Authority of the Deputy Minister's Position in the State Government Structure - deLima, Eliza Abraham; Tjiptabudy, Jantje; Nendissa, Renny Heronia (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The system of government adopted by Indonesia is the presidential system. Where is the position of the President as the head of state and head of government. In running the wheels of government, the President is assisted by state ministries. The number of state ministries is adjusted to the President's program in the field of government, as well as to support the performance of state ministries.Purposes of the Research: Explain the position of the deputy minister as stated in Article 10 of Law Number 39 of 2008 concerning State Ministries and understand the authority of the Deputy Minister in the organizational structure of the State Ministry.Methods of the Research: The type of research used is normative research. In this research, a statutory-regulatory approach (Statutory Approach) and a conceptual approach (Conceptual Approach) are used. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. Legal materials are qualitative.Results Main Findings of the Research: The position of Deputy Minister does not explicitly shift the position of Secretary to the Minister. The Deputy Minister and the Secretary General/Ministry have the same position as assistants to the Minister, but it is not normatively explained in the statutory regulations regarding whether the Deputy Minister shifts the position of Secretary to the Minister and there is overlapping authority between the position of the Deputy Minister and the Ministry Secretariat or Secretariat General in carrying out the ministry's duties.